Dysregulation of Leukaemia Inhibitory Factor (LIF) Signalling Pathway by Supraphysiological Dose of Testosterone in Female Sprague Dawley Rats During Development of Endometrial Receptivity - Allia Najmie Muhammad Yusuf; Mohd Fariz Amri; Azizah Ugusman; Adila A Hamid; Izzat Zulhilmi Abd Rahman; Mohd Helmy Mokhtar (Biomedicines)
Objective: This study investigated the effects of a supraphysiological dose of testosterone on uterine morphology and the regulation of the leukaemia inhibitory factor (LIF) signalling pathway during endometrial receptivity. Methods: In this study, 30 adult female Sprague–Dawley rats were divided into treatment and control groups. The treatment groups received subcutaneous injections of 1 mg/kg/day of testosterone from gestational day 1 to day 3, either testosterone alone or in combination with inhibitors (anastrozole, finasteride, or both). A control group of six untreated rats was maintained for comparison. Rats were euthanised on the evening of gestational day 4 to examine uterine morphological changes, gene expression and the distribution of proteins associated with the LIF signalling pathway (LIF, LIFR, JAK1 and STAT3) and MUC1 by quantitative polymerase chain reaction (qPCR) and immunohistochemistry (IHC), respectively. Results: The results of this study showed that the thickness of the endometrium and myometrium, as well as the number of glands, markedly decreased in all testosterone-treated rats. In addition, the mRNA levels of LIF, LIFR, JAK1 and STAT3 were significantly downregulated in response to supraphysiological testosterone treatment, while the mRNA of MUC1 was significantly upregulated. The IHC results were consistent with the mRNA data and confirmed the changes in protein distribution in all treatment groups. Conclusions: A supraphysiological dose of testosterone may impair endometrial receptivity through dysregulation of the LIF signalling pathway, potentially affecting fertility.